The Prospect of Waqf Al ‘Awaridh in the Contemporary Waqf Eco-System: A case of Malaysia - Nor Asiah Mohamad; Muhammad Laeba; Hisham Zaki El Tibli (Universitas YARSI, 2022)
This paper explains the concept of Waqf Al-Awaridh (Contingency Waqf) and its ruling in Shariah provision and the extent of the need for this type of Waqf. The paper will also address the importance of this type of Waqf from the perspective of the Shariah purposes (Maqasid Al-Shariah), including save the human souls and money from natural disasters (such as volcanoes and floods), pandemics and catastrophes such as the COVID-19 pandemic. The paper offers various proactive solutions in attending to frequent occurrence of natural disasters and catastrophes in many Muslim countries . Recently, there are many unexpected occurrences due to climate changes taking place in Malaysia and Pakistan, to mention a few examples. Waqf Al-Awaridh is presented as a social solution to mitigate the effects of disasters through the participation of some segments of society. The participation may be in the form of Waqf even for a small amount, regardless of the size or value of the property. This type of Waqf has not been well studied, and there is a need to raise awareness and spread the culture of Waqf al Awaridh among the Muslims especially in the countries which suffer from such natural disaster. This paper employed qualitative research methodology which involves content analysis; observations; discussions; internet explorations. The findings shall contribute to a new type of Waqf product and there should be a practical way to implement Waqf al Awaridh